Mineral deposition intervention through reduction of phosphorus intake suppresses osteoarthritic lesions in temporomandibular joint. Issue 9 (September 2021) - Duan, J.; Zhang, J.; Yang, H.; Liu, Q.; Xie, M.; Zhang, M.; Chu, Y.; Zhou, P.; Yu, S.; Chen, C.; Wang, M.
Summary: Objective: To explore the suppressing impact of low phosphorus intake on osteoarthritic temporomandibular joint and the possible mechanisms of nuclear acid injury in the insulted chondrocytes. Design: Chondrocytes were loaded with fluid flow shear stress (FFSS) with or without low phosphorus medium. Seventy-two mice (sampled at 3-, 7- and 11-wk, n = 6) and forty-eight rats (sampled at 12-wks for different testing purpose, n = 6) were applied with unilateral anterior crossbite (UAC) with or without low phosphorus diet. In the FFSS model, the Ca and P content, molecules related to nucleic acid degradation and the mineral-producing responses in chondrocytes were detected. The effect of culture dish stiffness on chondrocytes osteogenic differentiation was measured. In the UAC model, the content of Ca and P in serum were tested. The condylar cartilage ossification and stiffness were detected using micro-CT, scanning electron microscope and atomic force microscope. Results: FFSS induced nucleic acid degradation, Pi accumulation and mineral-producing responses in the cultured chondrocytes, all were alleviated by low P medium. Stiffer dish bottoms promoted the osteogenic differentiation of the cultured chondrocytes. UAC stimulated cartilage degeneration and chondrocytes nucleic acid damage, increased PARP 1 and serum P content, and enhanced ossification and stiffening of the cartilage, all were suppressed by low phosphorus diet (all, P < 0.05). Conclusion: Nucleic acid damage takes a role in phosphorus production in osteoarthritic cartilage, contributing to the enhanced mineralization and stiffness of the cartilage that in turn promotes cartilage degradation, which can be alleviated by low phosphorus intake.